Management Strategy, Character Formation and Modern Civilization Principles for Islamic Education in Indonesia - Neni Handayani; Ahmad Subagyo; M. Sofian Hadi; Wahyu Anggoro (Dinasti Publisher, 2025)
Islamic education in Indonesia plays a crucial role in character formation and civilization, but is faced with the challenges of relevance, quality, and adaptation in the modern era. This article outlines a comprehensive management strategy for Islamic educational institutions, which integrates modern management principles with Islamic values. The phenomenon of institutional diversity, quality issues, relevance dilemmas, traditional management, funding limitations, and the role of religious moderation is the background to the urgency of management. The theoretical basis includes general management functions (POAC) enriched with Islamic values such as Tauhid, Syura, Amanah, Ihsan, Adil, Maslahah, and Prophetic Leadership. The strategic planning methodology is emphasized through SWOT Analysis to identify strengths, weaknesses, opportunities, and threats, and Strategy Canvas as a visual tool to map operational models. The implementation of the strategy includes strategic planning based on Islamic vision, integrative curriculum management, professional human resource management, accountable financial management, technology-based infrastructure management, public relations and partnership management, and sustainable quality management. Despite facing challenges such as resistance to change and limited human resources, Islamic education has great opportunities through government support, demographic bonuses, and technological developments. The conclusion confirms that an effective management strategy, supported by the Strategy Canvas and SWOT Analysis, is the key to the progress of Islamic education, with suggestions for developing managerial capacity, standardization, utilizing technology, strengthening collaboration, innovation research, and policy advocacy.